Rhipicephalus (Boophilus) microplus (Canestrini, 1887) (Acari: Ixodidae): Acid phosphatase and ATPase activities localization in salivary glands of females during the feeding period - Nunes, Erika Takagi [UNESP]; Camargo Mathias, Maria Izabel [UNESP]; Bechara, Gervásio Henrique [UNESP] (Elsevier, 2006)
This study investigates the presence and the localization of acid phosphatase and ATPase in the salivary glands of Rhipicephalus (Boophilus) microplus female ticks during feeding. Semi-engorged females showed a larger amount of acid phosphatase compared to those at beginning of feeding, localized mainly in the apical portion of the secretory cells, and in the basal labyrinth of the interstitial cells. Ultrastructural observations also demonstrated its presence in secretion granules and inside some nuclei of secretory cells at beginning of feeding. Acid phosphatase in a free form probably has a hemolymph and/or ribosomal origin and participates in salivary gland secretion control. ATPase was detected in basal membrane of all types of acini and/or in the cytoplasm of the secretory cells at both feeding stages. The enzyme activities found strongly suggests that cell death by apoptosis occurs during the degenerative process. © 2006 Elsevier Inc. All rights reserved.
Keywords: Acid phosphatase; ATPase; Cattle-tick; Cytochemistry; Histochemistry; Rhipicephalus (Boophilus) microplus; Salivary glands; acid phosphatase; adenosine triphosphatase; animal cell; animal tissue; apoptosis; basement membrane; Boophilus microplus; controlled study; cytoplasm; enzyme activity; enzyme localization; feeding; female; hemolymph; nonhuman; priority journal; salivary gland; salivation; secretory cell; secretory granule; Acid Phosphatase; Adenosine Triphosphatases; Animals; Cattle; Cell Nucleus; Feeding Behavior; Female; Histocytochemistry; Microscopy, Electron, Transmission; Rhipicephalus; Salivary Glands; Secretory Vesicles; Acari; Boophilus; Ixodida; Ixodidae